Smoothed particle hydrodynamics : a meshfree particle method - Liu, G. R. (Gui-Rong) (World Scientific, 2003)
This is the first-ever book on smoothed particle hydrodynamics (SPH)and its variations, covering the theoretical background, numericaltechniques, code implementation issues, and many novel and interestingapplications.